IMPROVING BIOLOGY LEARNING OUTCOMES THROUGH PROBLEM-BASED LEARNING E-MODULES IN THE LABORATORY OF KUTACANE STATE SENIOR HIGH SCHOOL 1 - Zaini Hasan (Jurnal Penelitian Progresif, 2022)
The lack of innovative media in the biology learning process has a significant impact on the decline in learning outcomes of students at Kutacane 1 Public High School because they feel bored in the biology learning process. This became the basis for conducting this study. This study aims to describe the process of developing and validating PBL-based E-modules. This research is a development study using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The methods used for data collection include observation, interviews, and questionnaires. The data analysis techniques employed are qualitative descriptive analysis and quantitative descriptive analysis. The PBL-based E-module design is valid with: (a) blended learning is valid with: (a) expert review results with very good qualifications (90.6%), (b) expert review results of biology learning design with very good qualifications (97.1%), (c) the results of a review by learning media experts with a very good qualification (92.5%), (d) the results of individual trials with a very good qualification (95%), (e) the results of small group trials with a very good qualification (95%). Thus, this study shows that the validity of the problem-based learning-based E-module in terms of qualifications is very good and suitable for use in the biology learning process at SMA Negeri 1 Kutacane.